Antioxidant property, haematinic and biosafety effect of Ipomoea batatas lam. leaf extract in animal model - Benjamin Ogunma Gabriel (SpringerOpen, 2021)
Abstract Background Plant medicine was dated back for decades and has immensely contributed to the health care system in several countries. This present study evaluated in vitro antioxidant, anti-anaemic and biosafety properties of n-hexane leaf extract of Ipomoea batatas L. in an animal model. The antioxidant property of the extract was expressed by 1, 1-diphenyl-1-picrylhydrazyl (DPPH) with an appropriate method. The extract was orally administered at graded doses (125, 250 and 500 mg/kg body weight) to determine its effect on 40 mg/kg phenylhydrazine hydrochloride-induced anaemia in rats at days 1, 7 and 14 using a standard protocol. Acute and subacute toxicological evaluations were based on initial behaviour, mortality and histological examination of the organs. Results The antioxidant study of the extract showed 60.14% in the presence of DPPH and ascorbic acid. The haematological parameters (RBC, HGB, HCT, MCV, MCH and MCHC) significantly increased at p value < 0.05 in the treated groups compared with control groups. Specifically, there is a significant increase in the treatment groups, namely red blood cells (5.93, 6.78, 6.75), haematocrit (40.75, 44.05, 44.63) and haemoglobin (13.35, 14.70, 14.73), when compared with untreated control. Also, the results of the myeloid/erythroid ratio of the treated groups (20: 40, 21.7: 43.4 ratio) and (23. 3: 46.6 ratio) are compared with (15.0: 25.0 ratio) of 40 mg/kg phenylhydrazine and 25: 50 normal control of the bone marrow at day 14. No acute behavioural change or mortality was observed. Histological analysis exhibited normal physiological state of the visceral organs. Conclusions These findings support the folklore use of Ipomoea batatas L. leaf extract to reduce oxidative stress, treat anaemia and exhibit its safety at the highest doses of 500 mg/kg body weight.